Conceptual models for short‐eccentricity‐scale climate control on peat formation in a lower Palaeocene fluvial system, north‐eastern Montana (USA). Issue 3 (20th September 2017) - Noorbergen, Lars J.; Abels, Hemmo A.; Hilgen, Frederik J.; Robson, Brittany E.; de Jong, Edwin; Dekkers, Mark J.; Krijgsman, Wout; Smit, Jan; Collinson, Margaret E.; Kuiper, Klaudia F.
Abstract: Fluvial systems in which peat formation occurs are typified by autogenic processes such as river meandering, crevasse splaying and channel avulsion. Nevertheless, autogenic processes cannot satisfactorily explain the repetitive nature and lateral continuity of many coal seams (compacted peats). The fluvial lower Palaeocene Tullock Member of the Fort Union Formation (Western Interior Williston Basin; Montana, USA) contains lignite rank coal seams that are traceable over distances of several kilometres. This sequence is used to test the hypothesis that peat formation in the fluvial system was controlled by orbitally forced climate change interacting with autogenic processes. Major successions are documented with an average thickness of 6·8 m consisting of ca 6 m thick intervals of channel and overbank deposits overlain by ca 1 m thick coal seam units. These major coal seams locally split and merge. Time‐stratigraphic correlation, using a Cretaceous–Palaeogene boundary event horizon, several distinctive volcanic ash‐fall layers, and the C29r/C29n magnetic polarity reversal, shows consistent lateral recurrence of seven successive major successions along a 10 km wide fence panel perpendicular to east/south‐east palaeo‐flow. The stratigraphic pattern, complemented by stratigraphic age control and cyclostratigraphic tests, suggests that the major peat‐forming phases, resulting in major coal seams, were driven by 100 kyr eccentricity‐related climate cycles. Two distinct conceptual models were developed, both based on the hypothesis that the major peat‐forming phases ended when enhanced seasonal contrast, at times of minimum precession during increasing eccentricity, intensified mire degradation and flooding. In model 1, orbitally forced climate change controls the timing of peat compaction, leading to enhancement of autogenic channel avulsions. In model 2, orbitally forced climate change controls upstream sediment supply and clastic influx determining the persistence of peat‐forming conditions. At the scale of the major successions, model 2 is supported because interfingering channel sandstones do not interrupt lateral continuity of major coal seams.